A Deep Learning-Based Hybrid Approach to Detect Fastener Defects in Real-Time - Aydin, Ilhan; Sevi, Mehmet; Akin, Erhan; Guclu, Emre; Karakose, Mehmet; Aldarwich, Hssen (Univ Osijek, Tech Fac, 2023)
[Abstract Not Available]
Keywords: defect detection; deep learning; fastener; object detection; railway system